Content of α-, -interferon and neopterin in blood serum of women with parvovirus infection in different periods of pregnancy - Bondarenko, Natalia (ScienceRise: Medical Science, 2017)
The aim of the study was to determine α-, g-interferon (IFN) and neopterin levels in blood serum of pregnant women with a parvovirus infection. Methods and materials: There were examined 129 pregnant women, infected with a parvovirus В19, and 16 women with physiological pregnancy in I, II and III trimesters. Each group of pregnant women (I, II, III) was divided in two subgroups, depending on the presence or absence of clinical complications. The quantitative evaluation of α-, g-IFN and neopterin content in blood serum was realized by the method of immune-enzyme analysis. Results of research: Blood serum of infected pregnant women contained increased α-and g-IFN levels, most expressed at studying IFN-γ levels that reliably exceeded control indices in I-III groups in 3,4-2,9-2,1 times respectively. At the presence of clinical complications in different periods of pregnancy women demonstrated the reliably decreased α-IFN level and reliably increased g-IFN level compared with pregnant women without clinical complications. High levels of neopterin were revealed in blood serum of infected women that testifies to the activation of a monocytic link of the cellular immunity at the impact of g-IFN. At comparing the subgroups of pregnant women it was established, that changes of the neopterin level in blood serum relative to control values had the unidirectional character, but women with clinical complications of pregnancy demonstrated the more essential exceed of control values in different trimesters– in 2,9; 2,9 and 3,1 times. Conclusions. The increase of IFN-g and neopterin up to high values reflects the activation of a cellular immunity link and can play an important role in the pathogenesis of pregnancy complications